Analisis Pendapatan Dan Kelayakan Usahatani Kopi Arabika Di Desa Paraduan, Kecamatan Ronggurnihuta, Kabupaten Samosir - Deras, Stefanus (Universitas Katolik Santo Thomas Medan, 2025)
This study aims to: 1. Analyze the cost of production of Arabica coffee farming. 2. Analyze the income of Arabica coffee farming. 3. Analyze the feasibility of Arabica coffee farming. The research was conducted intentionally in Paraduan Village, Ronggurnihuta District, Samosir Regency, which is one of the coffee producing areas in Ronggurnihuta District, Samosir Regency. The research population as well as a sample of 30 farmer families, was determined by census. The results of the study showed that the total production cost per hectare was Rp 16,721,658.80 and the income was Rp 42,866,267.94, so that the net income per hectare was Rp 26,144,609.14. The R/C ratio per hectare was 2.56. This figure can be interpreted that by sacrificing a cost of Rp 1, farmers get an income of Rp 2.56, and the farmer's net income is 1.56, obtained from (Rp 2.56 - Rp 1). This shows that Arabica coffee farming in Paraduan Village is feasible